Sex Differences in Autism Spectrum Disorder: Diagnostic, Neurobiological, and Behavioral Features - Napolitano, Antonio; Schiavi, Sara; La Rosa, Piergiorgio; Rossi-Espagnet, Maria Camilla; Petrillo, Sara; Bottino, Francesca; Tagliente, Emanuela; Longo, Daniela; Lupi, Elisabetta; Casula, Laura; Valeri, Giovanni; Piemonte, Fiorella; et al. (Frontiers in Psychiatry, 2022)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental disorder with a worldwide prevalence of about 1%, characterized by impairments in social interaction, communication, repetitive patterns of behaviours, and can be associated with iper o ipo reactivity of sensory stimulation and cognitive disability. ASD comorbid features include internalizing and externalizing symptoms such as anxiety, depression, hyperactivity and attention problems. The precise aetiology of ASD is still unknown and it is undoubted that the disorder is linked to some extent to both genetic and environmental factors. It is also well documented and known that one of the most striking and consistent finding in ASD is the higher prevalence in males compared to females, with around 70% of ASD cases described being males. The present review looked into the most significant studies that attempted to investigate differences in ASD males and females thus trying to shade some light on the peculiar characteristics of this prevalence in terms of diagnosis, imaging, major autistic-like behavior and sex-dependent uniqueness. The study also discussed sex differences found in animal models of ASD, to provide a possible explanation of the neurological mechanisms underpinning the different presentation of autistic symptoms in males and females.